2017
DOI: 10.15673/fst.v11i4.732
|View full text |Cite
|
Sign up to set email alerts
|

Контамінація М’яса Тварин І Птиці Та Засоби Її Зниження

Abstract: Кафедра технічних систем та технологій тваринництва Харківський національний технічний університет сільського господарства ім. Петра Василенка проспект Московський, 45. м. Харків, Україна, 61050Анотація. У статті представлено результати з визначення рівня мікробної контамінації м'яса забійних тварин та птиці в процесі його технологічної переробки. Визначено, що кількість МАФАнМ та бактерій родини Enterobacteriaceae на поверхні туш яловичих варіює протягом робочого часу. Найнижче значення МАФАнМ реєст-рують піс… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Thus, it has been experimentally confirmed that the drug Orgasept has no suppressive effect on metabolic processes in rats. The use of effective and safe disinfectants is of paramount importance in providing the population with quality products of animal origin (Paliy et al, 2017(Paliy et al, , 2018d. One of the main criteria that determines the feasibility of using disinfectants in practical conditions is their environmental safety and low toxicity to staff and animals (Du et al, 2017;Bondarchuk et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it has been experimentally confirmed that the drug Orgasept has no suppressive effect on metabolic processes in rats. The use of effective and safe disinfectants is of paramount importance in providing the population with quality products of animal origin (Paliy et al, 2017(Paliy et al, , 2018d. One of the main criteria that determines the feasibility of using disinfectants in practical conditions is their environmental safety and low toxicity to staff and animals (Du et al, 2017;Bondarchuk et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Mold begins to multiply, forming white, grey, and black spots on the surface of the product, as a result of which the products of mold activity accumulate in meat products, an unpleasant odor appears (Mohapatra et al, 2017). Ways of contamination of raw materials, semi-finished products, and finished products by microorganisms are extremely diverse (Dukhnytskyi et al, 2011;Dudchik et al, 2013;Paliy, Rodionova and Palii, 2017). However, the most important source of additional microbial contamination of meat and meat products during refrigerated storage is the air of the refrigerator.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain quality and safe meat products is possible only with strict adherence to all technological and technical techniques that are implemented in meat processing enterprises of various forms of ownership (Paliy et al, 2018). Along with the quality control of raw materials, it should be paid great attention to the possible contamination of products by foreign microflora (Paliy et al, 2017;. Toxic secondary metabolites (mycotoxins), which are produced by micellar fungi, nowadays can be found on the surface of food, including bulks of sausage.…”
Section: Introductionmentioning
confidence: 99%